ASSOCIATION OF PRETERM LOW BIRTH WEIGHT WITH BLOOD CULTURE POSITIVITY AND ANTIMICROBIAL SENSITIVITY PATTERNS IN NEONATES WITH CLINICALLY SUSPECTED SEPSIS: A CROSS-SECTIONAL STUDY IN A TERTIARY CARE HOSPITAL - Shamiha Seraj; Marium Begum; Helena Begum; Rukonuzzaman Rukonuzzaman; Nabila Islam; Nazia Khan Majlish; Saher Seraj (World Journal of Biology Pharmacy and Health Sciences, 2026)
Background: Neonatal sepsis is a leading cause of neonatal morbidity and mortality in low- and middle-income countries. Prematurity and low birth weight (LBW) are recognized risk factors for invasive infection, but their combined effect on blood culture positivity and the antimicrobial sensitivity of the causative organisms is incompletely characterized in this setting. Objective: To determine the association between preterm LBW and blood culture positivity in neonates with clinically suspected sepsis, and to describe the bacterial profile and antimicrobial sensitivity patterns of the isolated organisms. Methods: This cross-sectional analytical study enrolled 180 neonates with clinically suspected sepsis admitted to the neonatal unit of Dhaka Central International Medical College & Hospital, Dhaka, Bangladesh over 12 months. Under aseptic precautions, 1–2 mL of blood was collected before antibiotic administration and processed by aerobic culture; organism identification and antimicrobial susceptibility testing were performed by the modified Kirby–Bauer disc-diffusion method interpreted per CLSI guidelines. Data were analyzed in SPSS v27; the chi-square test and odds ratios (OR) with 95% confidence intervals (CI) were used, with p < 0.05 taken as significant. Results: Blood culture was positive in 54/180 (30.0%) neonates. Positivity was significantly higher among preterm LBW neonates than among term normal-birth-weight neonates (39.6% vs 19.0%; OR 2.78, 95% CI 1.42–5.47; p = 0.003). Gram-negative organisms predominated (72.2%), led by Klebsiella pneumoniae (29.6%), Acinetobacter spp. (16.7%) and Escherichia coli (14.8%). Gram-negative isolates were largely resistant to ampicillin and third-generation cephalosporins but retained sensitivity to carbapenems and colistin; gram-positive isolates were uniformly sensitive to vancomycin and linezolid. Conclusion: Preterm LBW is significantly associated with a higher rate of blood culture positivity in neonatal sepsis. The predominance of multidrug-resistant gram-negative organisms underscores the need for local antibiogram-guided empirical therapy and strengthened antimicrobial stewardship.